The correct assignment of the lectotype of Vochysia guianensis (Vochysiaceae) - Shimizu, Gustavo Hiroaki; Gonçalves, Deise Josely Pereira; Litt, Amy; Simões, André Olmos; Yamamoto, Kikyo (Phytotaxa, 2016)
Vochysia Aublet (1775: 18) encompasses ca. 140 species, distributed from Mexico to southern Brazil. They are mainly large trees, with spurred yellow flowers, usually 3-petaled and with a single fertile stamen (Kawasaki 2007). The genus was described by Aublet (1775) in his work on plants from French Guiana as ‘Vochy’, taken from a native name among the Caribs, and after several latinizations the form ‘Vochysia’, proposed by Poiret (1808), was conserved.